Zur Überlieferung von Hans von Gersdorffs Feldtbuch der Wundarzney: die Handschrift Kopenhagen GKS 1663 4to und ihr Verhältnis zu den Druckfassungen - Chiara Benati (Filologia Germanica, 2025)
The surgical handbook known as Feldtbuch der Wundarzney by the Strasburgian field surgeon Johannes (Hans) von Gersdorff is one of the earliest medical texts printed in the High German language area. During the Early Modern Age this text enjoyed great popularity as witnessed by the high number of editions which followed the first one: eleven or twelve in quarto and three or four in folio in a timespan running from 1526 to 1606. The Feldtbuch was also translated into Dutch (1591, 1593, 1605 and 1622) and probably into Latin. While the printed tradition of the surgical handbook has been repeatedly taken into consideration by scholars, less attention has been paid to its manuscript tradition. Fragments of von Gersdorff’s work can be found in four late manuscript collections of medical and surgical texts: Lucerne, Zentral- und Hochschulbibliothek, KB Pp 27 4to; Kassel, Universitäts- und Landesbibliothek, 8vo Ms. med. 6; Copenhagen, Det Kongelige Bibliotek, Thott 253 8vo; Copenhagen, Det Kongelige Bibliotek, GKS 1663 4to. This last is particularly interesting for the study of the text tradition and circulation in Europe, because it contains a large portion of a Low German version of the surgical handbook. The aim of this study is to examine Copenhagen GKS 1663 4to and to compare it with the High German and Dutch printed versions of the Feldtbuch in order to identify the source of the Low German translation contained in the manuscript. Special attention is paid to the structure of the fragment and to the possible reasons underlying the selection of the portions of text transcribed in Copenhagen GKS 1663 4to.